Characterisation and Identification of Avian Influenza Virus (AI) - Hewajuli, Dyah Ayu; Dharmayanti, NLP I (Indonesian Bulletin of Animal and Veterinary Sciences, 2008)
Avian Influenza is caused by Influenza A virus which is a member of Orthomyxoviridae family. Influenza A virus is enveloped single stranded RNA with eight-segmented, negative polarity and filament or oval form, 50 â 120 by 200 â 300 nm diameters. Influenza A viruses have been found to infect birds, human, pig, horse and sometimes in the other mammalian such as seal and whale. The viruses are divided into different subtypes based on the antigenic protein which covers the virus surface i.e. Haemaglutinin (HA) and Neuraminidase (NA). In addition, the nomenclature of subtype virus is based on HA and NA i.e HxNx, for example H5N1, H9N2 and the others. According to pathogenic, it could be divided into two distinct groups, they are Highly Pathogenic Avian Influenza (HPAI) and Low Pathogenic Avian Influenza (LPAI). The Avian Influenza viruses have been continuously occurred and spread out in some continents such us America, Europe, Africa and Asian countries. The outbreak of Avian Influenza caused high mortality on birds and it has been reported that in human case Avian Influenza subtype H5N1 virus has caused several deaths. To anticipate this condition, an effort to prevent the transmission of Avian Influenza is needed. These strategic attempts include biosecurity, depopulation, vaccination, control of virus movement, monitoring and evaluation. Laboratory diagnostic plays an important role for successful prevention, control and eradication programs of Avian Influenza. Recently, there are two diagnostic methods for Avian Influenza. They are conventional (virological diagnosis) and molecular methods. The conventional method is usually used for initial diagnostic of Avian Influenza. The conventional method takes more time and more costly, whereas the molecular method is more effective than conventional method. Based on the available diagnostic technique, basically diagnostic of Avian Influenza is done by serology test, isolation and identification as well as pathogenicity test. Â  Key words: Avian Influenza, Characterisation, Identification, Laboratory Diagnostic